The New Silk Road Diplomacy : China's Central Asian Foreign Policy since the Cold War - Karrar, Hasan H. (Hasan Haider), 1973- (Book collections on Project MUSE., 2009)
"With the collapse of the Soviet Union, newly independent states sprang up along China's western frontier. Suddenly, Beijing was forced to confront internal challenges to its authority at its border as well as international competition for energy and authority in Central Asia. Hasan Karrar traces how China cooperated with Russia and the Central Asian republics seeking to stabilize the region, facilitate commerce, and build an energy infrastructure. He also shows how this multilateral approach brought Beijing into direct competition with the United States, which views Central Asia as vital to its strategic interests."--Jacket.